The significance of strong ion gap for predicting return of spontaneous circulation in patients with cardiopulmonary arrest - Kaneko, Minoru; Hagiwara, Shuichi; Aoki, Makoto; Murata, Masato; Nakajima, Jun; Oshima, Kiyohiro (Central European journal of medicine, 2017)
Useful parameters that can predict return of spontaneous circulation (ROSC) in patients with cardiopulmonary arrest (CPA) have not been established. We previously reported the usefulness of anion gap (AG) and albumin-corrected anion gap (ACAG) calculated from a blood sample obtained on arrival at the hospital for the prediction of ROSC. Otherwise, it has been reported that strong ion gap (SIG), which shows the difference between the levels of fully dissociated cations and anions in the serum, is useful to predict the prognosis of critically ill patients. This was a prospective and observational clinical study. Patients with CPA transferred to the emergency department of our hospital between January 2013 and December 2014 were evaluated. Patients were divided into two groups: patients who obtained ROSC [ROSC(+) group] and those who did not [ROSC(−) group]. We compared AG, ACAG and SIG between the two groups. A total of 170 patients were enrolled. Fifty patients were included in the ROSC(+) group, and the remaining 120 in the ROSC(−) group. Both AG and ACAG were significantly better in the ROSC(+) group; however, there was no significant difference in SIG between the two groups. The area under the receiver operating characteristic curves (AUC) for ROSC of both AG and ACAG were almost the same (0.72 and 0.708, respectively); the AUC of SIG (0.57) was inferior to those of AG and ACAG. Our results suggest that AG and ACAG can better predict ROSC following cardiopulmonary resuscitation (CPR) compared with SIG.